Medieval Literature: A Very Short Introduction - Treharne, Elaine M. (New York Oxford University Press, 2015)
Looking at literature from Medieval Britain and Ireland, including Anglo-Latin and Anglo-Norman poetry, prose and drama, this Very Short Introduction covers the earliest beginnings of print culture, and considers major themes of these works, such as sin and salvation, kingship and authority, myth and the monstrous.
Includes Index and Illustrations.
Keywords: English literature -- Old English, ca. 450-1100 -- Introduction